2022
DOI: 10.1371/journal.pone.0271689
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of abatacept enhances IL-35+ and IL-10+ producing Bregs in lung tissues of ovalbumin-sensitized asthmatic mice model

Abstract: Backgrounds Treating asthmatic rheumatoid arthritis patients with abatacept has been shown to associate with better control of asthma symptoms. However, the mechanism behind that is not investigated. Methods Ovalbumin (OVA)- sensitized BALB/c female mice were treated intranasally (IN) or intraperitoneally (IP) with abatacept 4 hrs before the OVA challenge. The effects of abatacept IN or IP on the lungs and blood levels of Tregs and Bregs and their production of immunosuppressive cytokines, were determined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Although patients with and without auto-Abs to type I IFNs did not show overt clinical differences in COVID-19, they differed in plasma IL-17 levels (Table 1 ). An in vivo study demonstrated an inverse association between lung tissue levels of IL-17 and LAG3 cTregs/uTregs 20 , which might explain the lower frequency of LAG3 cTregs/uTregs in the blood of these patients. However, further research is needed to fully understand the mechanistic link between LAG3 expression and IL-17 regulation.…”
Section: Discussionmentioning
confidence: 97%
“…Although patients with and without auto-Abs to type I IFNs did not show overt clinical differences in COVID-19, they differed in plasma IL-17 levels (Table 1 ). An in vivo study demonstrated an inverse association between lung tissue levels of IL-17 and LAG3 cTregs/uTregs 20 , which might explain the lower frequency of LAG3 cTregs/uTregs in the blood of these patients. However, further research is needed to fully understand the mechanistic link between LAG3 expression and IL-17 regulation.…”
Section: Discussionmentioning
confidence: 97%
“…Abatacept, a fusion CTLA‐4 protein approved for rheumatoid and psoriatic arthritis, has been shown to influence the IL‐10 axis. Intranasal administration of abatacept in asthmatic mice showed increased IL‐10‐ and IL‐35‐producing Bregs and LAG3+ Tregs 94 . Administration of the protein Alt a 1, a major allergen found in fungi (specifically Alternaria alternata ), was shown to decrease asthmatic symptoms and increase Breg levels in a mouse model 95 .…”
Section: Developing Breg‐targeted Immunotherapiesmentioning
confidence: 98%
“…Intranasal administration of abatacept in asthmatic mice showed increased IL-10-and IL-35-producing Bregs and LAG3+ Tregs. 94 Administration of the protein Alt a 1, a major allergen found in fungi (specifically Alternaria alternata), was shown to decrease asthmatic symptoms and increase Breg levels in a mouse model. 95 Last, IL expression is known to be regulated by epigenetic shifts in histone acetylation/deacetylation.…”
Section: Aitmentioning
confidence: 99%
“…Previously, we and others have confirmed the pathophysiology of allergic airway inflammation in the mouse model of asthma. [12,[28][29][30][31] However, the initial trigger in the development of AAI in an asthma mouse model, especially with respect to gut-lung axis, has not yet been studied. Therefore, to validate the development of AAI in pre-challenge and post-challenge conditions, we investigated the mRNA expression of Th2 cytokines in lung tissues.…”
Section: Translocation Of Type 2 Inflammation From Gut To Lung In Mou...mentioning
confidence: 99%